Design of biogas digester with thermophilic pretreatment for reducing fruits wastes - Budy Rahmat; Ida Hodiyah; Apip Supriadi; Memet Hikmat; Gilang Purnama (International Journal of Recycling of Organic Waste in Agriculture)
Purpose This study aimed to design a biogas digester that works thermophilically and mesophilically and tested its performance to produce biogas and digestate. Method This study used some experimental methods, which consists of: (1) design and construction process of the digester which can facilitate the thermophilic process as a pretreatment of the feedstock and the anaerobic digestion process of the substrate; (2) determination of the quantity of biogas, liquid digestate, and compost; and (3) testing digestate quality as a liquid organic fertilizer for Ipomoea reptans. Results The built biogas digester was able to accommodate thermophilic digestion that runs intensely in the pretreatment tank, where the complex organic compounds, namely cellulose and hemicellulose, decomposed intensively, so that it becomes a suitable substrate. As raw material, every 4 kg of banana waste, can produce biogas, digestate and dry compost of 10, 200 cm3 (highest yield), 5900 mL, and 1420 g, respectively. The highest Ipomoea reptans growth was achieved by digestate treatment from banana waste. Conclusion Thermophilic pretreatment could shorten the processing time to 3 days. Digestate treatment as a liquid organic fertilizer is able to provide a better supply of nutrients for plants.